The modern pillars of Circular Economy - matarazzo, agata (Archives of Business Research, 2018)
Relationship between industry and environment is crucial for industrial business performance. Environmental impacts have incrementally increased pressure on industrial businesses. Looking back to the beginning of the industrial revolution, mass production of goods was enabled by new manufacturing methods resulting in products with high availability and low costs. Consequently, due to new consumer societies and staggering growth in industrial activity, emissions to environment, solid waste generation and landfill have become increasingly severe. In addition, due to a growing world population and especially strong middle-class growth the demand for resources is expected to rise rapidly indicating a rising consumption of natural resources. This paper shows the modern concepts of the circular economy and industrial ecology, emphasiyng the benefits of industrial symbiosis